An Epigenetic Alphabet of Crop Adaptation to Climate Change - Guarino, Francesco; Cicatelli, Angela; Castiglione, Stefano; Agius, Dolores R.; Orhun, Gul Ebru; Fragkostefanakis, Sotirios; Leclercq, Julie; Dobránszki, Judit; Kaiserli, Eirini; Lieberman-Lazarovich, Michal; Sõmera, Merike; Sarmiento, Cecilia; et al. (Frontiers in Genetics, 2022)
Crop adaptation to climate change is in part attributed to epigenetic mechanisms that response of plants to abiotic and biotic stresses. Although recent studies has allowed gaining insight into the nature of these mechanisms, epigenetics remains under-investigated and still poorly understood in many plants, but is one of the most fascinating research area. Epigenetic modifications are traditionally divided into two main groups-DNA methylation and histone post translational modifications- that lead to chromatin remodeling and to the regulation of genome functioning during development and in response to environmental cues. In this review, we outline the most recent and interesting findings on crop epigenetic responses to environmental stresses and stimuli that are most relevant to climate change. In addition, we discuss a speculative point of view trying to decipher the “epigenetic alphabet” underlying mechanisms of crop adaptation to climate change. The understanding of these molecular mechanisms will pave the way to new strategies to design and implement the next generation of cultivars with a broad range of tolerance/resistance to abiotic and biotic stresses as well as balanced agronomic traits, limited loss of (epi)genetic variability, and improved plant stress and disease management.